PENGEMBANGAN PERANGKAT PEMBELAJARAN DAN LEMBAR KERJA SISWA BERBASIS PENDEKATAN PMR SISWA KELAS VII SMP NEGERI 14 MERANGIN - Yohanes; Hayatul Mughiroh; Hidayati Rais (Mat-Edukasia, 2017)
The purpose of this study is to produce learning devices and LKS based on a realistic, valid and effective approach to realistic mathematics education. This learning tool is expected to be able to improve student learning activities and outcomes. This type of research is development research using a 4-D model consisting of 4 stages, namely 1) defining, 2) designing (design), 3) developing, and 4) disseminating (disseminate). The contextual mathematics learning tools developed are Student Worksheets (LKS) and Learning Implementation Plans (RPP). Validation is done by experts in mathematics education, basic education and language. The practicality of learning devices is investigated by observing the implementation of learning, filling the practical questionnaire by students, and conducting interviews with students and teachers. To see its effectiveness is done by observing the activities and student learning outcomes. The collected data was analyzed descriptively. The results showed that the learning tools of the realistic mathematics education approach (PMR) produced were valid in terms of their constructs and contents for Class VII of Merangin 14 Middle School. Contextual mathematics learning tools can be said to be practical in terms of the implementation of learning and effective on the activities and learning outcomes of students for class VII. Learning tools for realistic mathematics education approaches (PMR), have been tested and implemented. Based on the results of the trial and implementation it can be said that the learning tools approach to realistic mathematics education (PMR) are valid, practical and effective Keywords: Learning Devices, Student Worksheets (LKS) and Realistic MathematicsEducation Approach (PMR)